Geochemical transformation of soil cover and woody vegetation in the largest industrial and transport center of Northern Mongolia (Darkhan). (August 2019) - Kosheleva, Natalia E.; Timofeev, Ivan V.; Kasimov, Nikolay S.; Sandag, Enkh-Amgalan
Abstract: Geochemical changes in the surface soil horizons and in the trace element composition of the leaves of poplar hybrids under the influence of emissions from the industry and transport hub of the city of Darkhan (Mongolia) were studied. Based on the data of the geochemical survey, priority pollutants in various land-use zones of the city and regularities of their spatial distribution were determined. Atmospheric emissions from thermal power and metallurgical plants, and leather factory resulted in the accumulation of Zn, As, Cd, Cu, and Ni in the soils and poplar leaves. The widespread distribution of yurt quarters utilizing brown coal from Sharyngol and Baganur mines for domestic purposes led to the formation of the areas with abnormally high concentrations of Zn, Cd, Sb, Ba, and Sn in the soils and Cd, V, Ni, and Cu in the leaves of poplar. An increase in the urban population and in the number of vehicles that, until recently, used leaded gasoline caused increased concentrations of Zn, Cd, Cu, and Ba in the soils and of Zn and Pb in the leaves of poplar. Ba and V represent the greatest danger in Darkhan; their coefficients of ecological hazard exceed established international standards by two or more times. Multielemental pollution of surface soil horizons is characterized by a low level of environmental risk throughout the city, except for the local anomalies near the metallurgical plant and the thermal power station. It is known that the main route of admission of potentially toxic elements into assimilating organs of urban vegetation is foliar absorption. The ratios of trace elements in poplar leaves attest to the balanced metabolic processes in poplar hybrids and their generally satisfactory state, except for the local anomalies close to those established for the soils. The Fe/Mn and Pb/Mn ratios are most balanced under the background conditions and display maximum deviation from this state in the industrial zone of the city. The Cu/Zn ratio found in the studied woody plants indicates the imbalance in provision of the enzyme synthesis because of Zn deficiency, detected in the inner yards of the residential high-rise zone. Highlights: Distribution of trace elements in urban topsoils and poplar leaves was determined(83). Thermal power plant formed the most pronounced multi-elemental anomaly in the soils(85). Emissions of household stoves enhance content of Cd, V, Ni, Cu in poplar leaves(81). Ratios of trace elements attest to satisfactory state of plants almost everywhere(83).